2021
DOI: 10.9734/jpri/2021/v33i47b33171
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice towards COVID-19 Infection during Pregnancy among Antepartum Women

Abstract: Background: Pregnant women are more susceptible to developing severe cases of COVID-19. They need to be more careful during the antepartum, intrapartum, and postpartum periods to prevent untoward outcomes. As no definite treatment for COVID- 19 has yet been proven,  the only effective approach to prevent unfavorable outcome is by increasing awareness of  COVID-19 among pregnant women and by encouraging them to follow the necessary prevention methods. This study was done to know, if the adherence to the recomme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…[16][17][18] Increased disease awareness and positive attitude and behavior have been found to effectively control the spread of contagious diseases. [19][20][21] Some studies have shown that the majority of pregnant women have sufficient knowledge, positive attitudes, and practices for preventive behaviors against COVID-19 [21][22][23][24] ; others justified the need to raise awareness and recommend health education. [25][26][27] Of the few studies conducted to define the knowledge, attitudes, and practices (KAP) of pregnant women during the COVID-19 pandemic in Iran, Maharlouei et al reported that over 80% of the questions were answered correctly by 44.3% of the population studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18] Increased disease awareness and positive attitude and behavior have been found to effectively control the spread of contagious diseases. [19][20][21] Some studies have shown that the majority of pregnant women have sufficient knowledge, positive attitudes, and practices for preventive behaviors against COVID-19 [21][22][23][24] ; others justified the need to raise awareness and recommend health education. [25][26][27] Of the few studies conducted to define the knowledge, attitudes, and practices (KAP) of pregnant women during the COVID-19 pandemic in Iran, Maharlouei et al reported that over 80% of the questions were answered correctly by 44.3% of the population studied.…”
Section: Introductionmentioning
confidence: 99%
“…Increased disease awareness and positive attitude and behavior have been found to effectively control the spread of contagious diseases 19–21 . Some studies have shown that the majority of pregnant women have sufficient knowledge, positive attitudes, and practices for preventive behaviors against COVID‐19 21–24 ; others justified the need to raise awareness and recommend health education 25–27 …”
Section: Introductionmentioning
confidence: 99%